DNA methyltransferase 1/3a overexpression in sporadic breast cancer is associated with reduced expression of estrogen receptor‐alpha/breast cancer susceptibility gene 1 and poor prognosis. Issue 9 (25th January 2014) - Yu, Zhaojin; Xiao, Qinghuan; Zhao, Lin; Ren, Jie; Bai, Xuefeng; Sun, Mingli; Wu, Huizhe; Liu, Xiaojian; Song, Zhiguo; Yan, Yuanyuan; Mi, Xiaoyi; Wang, Enhua; et al.
<x xml:space="preserve">Abstract</x> DNA methyltransferases (DNMTs), including DNMT1, 3a, and 3b, play an important role in the progression of many malignant tumors. However, it remains unclear whether expression of DNMTs is associated with the development of breast cancer. This study aimed to explore the clinical significance of DNMT proteins in sporadic breast cancer. We investigated the expression of DNMT1, 3a, and 3b in 256 breast cancer and 36 breast fibroadenoma, using immunohistochemistry. The expression of DNMT1 and 3a was significantly higher in breast cancer than in fibroadenoma. In breast cancer, the expression of DNMT1 was significantly correlated with lymph node metastasis (P = 0.020), and the expression of DNMT3a and 3b was significantly correlated with advanced clinical stages (P = 0.046 and 0.012, respectively). Overexpression of DNMT1/3a was correlated with promoter hypermethylation and reduced expression of ERα and BRCA1. The expression levels of DNMT1 or DNMT3a were associated with a significantly shorter DFS or OS in a subgroup of breast cancer patients (patients with the age ≤50 years old, ERα‐negative status, or HER2‐postive status). The expression of DNMT1 or a combined expression of DNMT1 and 3a was associated with poor prognosis in patients who received chemotherapy and endocrine therapy, but not in patients who received chemotherapy alone. These findings suggest that DNMT1 and 3a may be involved in the progression and prognosis of sporadic breast cancer. © 2014 Wiley Periodicals, Inc.